Accelerating newborn survival in Ghana through a low-dose, high-frequency health worker training approach: a cluster randomized trial - Patricia P. Gomez; Allyson R. Nelson; Amos Asiedu; Etta Addo; Dora Agbodza; Chantelle Allen; Martha Appiagyei; Cynthia Bannerman; Patience Darko; Julia Duodu; Fred Effah; Hannah Tappis (BMC, 2018)
Abstract Background Newborn deaths comprise nearly half of under-5 deaths in Ghana, despite the fact that skilled birth attendants (SBAs) are present at 68% of births, which implies that evidence-based care during labor, birth and the immediate postnatal period may be deficient. We assessed the effect of a low-dose, high-frequency (LDHF) training approach on long-term evidence-based skill retention among SBAs and impact on adverse birth outcomes. Methods From 2014 to 2017, we conducted a cluster-randomized trial in 40 hospitals in Ghana. Eligible hospitals were stratified by region and randomly assigned to one of four implementation waves. We assessed the relative risks (RRs) of institutional intrapartum stillbirths and 24-h newborn mortality in months 1-6 and 7-12 of implementation as compared to the historical control period, and in post-intervention facilities compared to pre-intervention facilities during the same period. All SBAs providing labor and delivery care were invited to enroll; their knowledge and skills were assessed pre- and post-training, and 1 year later. Results Adjusting for region and health facility type, the RR of 24-h newborn mortality in the 40 enrolled hospitals was 0·41 (95% CI 0·32-0·51; p < 0.001) in months 1-6 and 0·30 (95% CI 0·21-0·43; p < 0·001) in months 7-12 compared to baseline. The adjusted RR of intrapartum stillbirth was 0·64 (95% CI 0·53-0·77; p < 0·001) in months 1-6 and 0·48 (95% CI 0·36-0·63; p < 0·001) in months 7-12 compared to baseline. Four hundred three SBAs consented and enrolled. After 1 year, 200 SBAs assessed had 28% (95% CI 25-32; p < 0·001) and 31% (95% CI 27-36; p < 0·001) higher scores than baseline on low-dose 1 and 2 content skills, respectively. Conclusions This training approach results in a sustained decrease in facility-based newborn mortality and intrapartum stillbirths, and retained knowledge and skills among SBAs after a year. We recommend use of this approach for future maternal and newborn health in-service training and programs. Trial registration Retrospectively registered on 25 September 2017 at Clinical Trials, identifier NCT03290924.